Alashinols F and G, two lignans from stem bark of Syringa pinnatifolia. Issue 13 (3rd July 2017) - Feng, Xiao; Su, Guozhu; Ye, Yunyun; Zhang, Ruifei; Yang, Xinyao; Du, Bingzhao; Peng, Bing; Tu, Pengfei; Chai, Xingyun
Abstract: Two new lignans, alashinols F and G (1 and2 ), together with two known analogues (−)-secoisolariciresinol (3 ) and meso -secoisolariciresinol (4 ) were isolated from the stem bark of Syringa pinnatifolia, a Mongolian folk medicine with anti-myocardial ischaemic effects. Their structures were elucidated on basis of spectroscopic data analyses, including MS and 1D and 2D NMR, and their absolute configurations were elucidated on the basis of experimental and calculated electronic circular dichroisms. The in vitro anti-inflammation and anti-hypoxia evaluations were also discussed. Abstract :